Developing an ownership culture with employee share purchase plans: Evidence from France - Nicolas Aubert (Zeitschrift für Personalforschung (ZfP), 2008)
Positive effects of employee participation on organizational performance are closely linked to the implementation of a specific corporate culture always referred to as 'ownership culture'. This issue can be stimulated through employee share purchase plans (ESPP). This article will investigate how to implement a successful ESPP. In order to do so, we review the literature on employees' investment decisions about their employer's shares. We present in another section the data and methodology of the empirical study. We have conducted semi-structured interviews with French experts specialising in ESPP's implementation. We use the content analysis technique to analyse these interviews. Another section is dedicated to presenting the results of the qualitative research. We find that - offering leveraged employee ownership funds - ESPP's general characteristics, - allowing employees to transfer their deferred profit sharing and gain sharing bonuses into the ESPP - discounting the share price, - giving employees payment facilities, - marketing expenses are particularly successful in stimulating employees' investment. In the last section, we discuss and comment on our results. – – Positive Effekte der Mitarbeiterbeteiligung auf die Unternehmensleistung sind eng gebunden an die Implementierung einer spezifischen Unternehmenskultur, die gewöhnlich als Eigentümerkultur bezeichnet wird. Die Entwicklung einer solchen Kultur kann durch Mitarbeiteraktienpläne (ESPPs) angeregt werden. Dieser Artikel untersucht, wie sich ESPPs erfolgreich implementieren lassen. Nach einer Analyse der Literatur über die Entscheidungen von Mitarbeitern zur Investition in ihr Unternehmen wird über eine empirische Studie berichtet: In halbstandardisierten Interviews wurden französische Experten für die Implementierung von ESPPs befragt, die Interviews wurden anschließend mit inhaltsanalytischen Techniken ausgewertet. Besonders wirkungsvoll zur Anregung von Investitionen von Mitarbeiterseite sind demnach das Angebot kreditfinanzierter Mitarbeiterkapitalbeteiligung, Mitarbeitern die Möglichkeit zu geben, ihre aufgeschobene Gewinnbeteiligung und ihre Zahlungen aus Leistungsbeteiligungen in ESPPs zu übertragen, Diskontierung des Aktienpreises, den Mitarbeitern spezielle Bezahlungskonditionen einzuräumen sowie ausgeprägtes Marketing. Die Ergebnisse werden diskutiert und kommentiert.
Keywords: 330; employee share purchase plan; employee share ownership; ownership culture; Aktienoption; Frankreich